Identification of the root-knot nematode species associated with Carica papaya - Stella Nostra Gracia Plena; Siwi Indarti; Ani Widiastuti; Nugroho Susetya Putra (Society for Indonesian Biodiversity, 2022)
Abstract. Plena SNG, Indarti S, Widiastuti A, Putra NS. 2022. Identification of the root-knot nematode species associated with Carica papaya.Biodiversitas 23: 6212-6217. Root-knot nematodes (Meloidogyne spp.) are important economic pests causing low production and yield losses in horticultural crops. Meloidogyne spp. is widespread and regarded as a major pest since they are found all over the world in a variety of geographic locations, most frequently found in tropical and subtropical climate zones. They are obligate parasites that feed on various plants, including papaya and other horticultural plants. They are root-galling in host plants. Many species of root-knot nematodes may be found in a suitable environment. Therefore, accurate identification of the root-knot nematode species in papaya plants is important for developing and applying control and management measures. Surveys and sampling of nematodes on papaya plants were performed at the Agrotechnology Innovation Center, Universitas Gadjah Mada, the Special Region of Yogyakarta, Indonesia, and its surroundings. Identification was performed both morphologically (based on the perineal pattern of female nematodes) and molecularly (using root-knot nematode species-specific primers). The results revealed that the species of root-knot nematode associated with papaya plants was Meloidogyne javanica based on the perineal pattern of female nematodes, specifically the lateral lines. This finding was also supported by the results of the DNA amplification at 670-bp product using specific primers for M. javanica (FJav/RJav). Consequently, plant protection efforts will need to focus on minimizing M. javanica damage in papaya cultivation.